Kedudukan Anak Luar Kawin dalam Sistem Waris Adat Sabu: Praktik Bui pa Studi atas kepue - Rayi Kharisma Rajib; Intan Salwa Puspita Hapsari; Dewi Latifah Azzahra Noor (JURNAL ILMIAH NUSANTARA, 2026)
Children born out of wedlock often face limited rights under various legal systems, including both national and customary law. In the context of the Sabu indigenous community in East Sabu Subdistrict, Sabu Raijua Regency, there is a unique concept known as bui pa kepue, which literally means "a child who fell from a tree," referring to a child born outside a marriage recognized as valid under customary law. In contrast to the stigma commonly prevalent in broader society, Sabu customary law grants specific recognition to bui pa kepue children. This article aims to analyze the position of bui pa kepue children within the framework of Sabu customary law and its implications for inheritance rights. This study employs a normative legal methodology with conceptual, statutory, and anthropological approaches, supported by a literature review of relevant customary law and positive law sources. The results indicate that bui pa kepue children receive social recognition and inheritance rights through the maternal line; however, this recognition remains limited, as reflected in symbolic restrictions within customary rituals and the absence of a legal relationship with the paternal line. The Sabu customary system does not entirely discriminate against children born out of wedlock, but it does not yet fully guarantee equality of rights, particularly in the context of cross-lineage inheritance.